2024
DOI: 10.1186/s12872-024-03773-7
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic characteristics of coronary artery disease in patients undergoing diagnostic coronary angiography at a tertiary hospital in Tanzania

John R. Meda,
Happiness L. Kusima,
Ng’weina F. Magitta

Abstract: Background Coronary artery disease (CAD) is an important cause of global burden of disease. There is a paucity of data on the burden and risk factors for CAD in sub-Saharan Africa (SSA), despite the rising trends in the shared risk factors across regions. The recent introduction of cardiac catheterization laboratory services in SSA could shed light on the burden of CAD in the region. We aimed to assess the angiographic characteristics among patients undergoing diagnostic coronary angiography (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A similar retrospective 2-year chart review of 728 patients ≥ 18 years of age who underwent CAG in Tanzania found similar clinical characteristics in terms of age and gender association with CAD, with a mean age of 59 ± 10.83 and a signi cantly higher prevalence of CAD in males versus females (34.18% in males versus 15.50% in females). 22…”
Section: Age and Sexmentioning
confidence: 99%
“…A similar retrospective 2-year chart review of 728 patients ≥ 18 years of age who underwent CAG in Tanzania found similar clinical characteristics in terms of age and gender association with CAD, with a mean age of 59 ± 10.83 and a signi cantly higher prevalence of CAD in males versus females (34.18% in males versus 15.50% in females). 22…”
Section: Age and Sexmentioning
confidence: 99%